Enacting Alcohol and Other Drug (Testing)-Related Harms in an Australian Drug Court. (September 2019) - Sarmiento, Eliana; Seear, Kate; Fraser, Suzanne
Alcohol and other drug testing is used in a range of environments including workplaces, schools, sporting tournaments, substance treatment and criminal justice system settings. It is also the cornerstone of the drug court model. Despite its centrality, it has received little scholarly attention. In this article, we address this gap through a study of how the drug-testing regime unfolds at one Australian drug court. Based on ethnographic observation, qualitative interviews with drug court participants, and analysis of drug court documents, this article examines how participants experience drug testing. Drawing on Carol Bacchi's poststructuralist policy analysis framework, we examine how the "problem" of substance "dependence" is conceptualized in one drug court's approach to drug testing, and we consider some of the effects of the policy. We argue that the everyday and seemingly mundane ritual of urination becomes a core technique for the governance of drug court subjects and note that the testing regime is onerous, regimented, and invasive. We also trace some of the effects of this policy and its implementation for participants. We suggest that the urine-testing regimen might operate counterproductively, intensifying participants' involvement with the criminal justice system. Its reliance on an abstinence model may heighten exposure to substance-related harms and segregate drug court participants from the "rest of society, " inhibiting other aspects of their lives, including their relationships and employment prospects. Overall, we argue that these effects are at odds with the stated purposes of the drug court. We conclude with some reflections on claims about the therapeutic value and potential of drug courts and suggest opportunities for reform.